Developing procedures for assessment of ecological status of Indian River basins in the context of environmental water requirements - Smakhtin, Vladimir U.; Arunachalam, M.; Behera, S.; Chatterjee, A.; Das, S.; Gautam, P.; Joshi, G.D.; Sivaramakrishnan, K.G.; Unni, K.S. (International Water Management Institute, 2007)
This report attempts to introduce a prototype scoring system for the ecological status of rivers in India and illustrate it through the applications in several major river basins. This system forms part of the desktop environmental flow assessment and is based on a number of indicators reflecting ecological condition and sensitivity of a river. The unique aspect of this study is that it interprets, for the first time, the existing ecological information for Indian rivers in the context of environmental flow assessment. The report targets government departments, research institutions and NGOs which are engaged in environmental flow management and associated policy development, and suggests some subsequent steps in environmental flow work in India.